Synthesis, and Structural Characterization of (E)-1-(4-((2-(2,4-Dinitrophenyl) hydrazono) methyl)phenyl) piperidine: A Combined Spectroscopic and Computational Study - Sapkota, Kamal Raj; Kumari, Shilpi; Alam, Zeba; Faizi, Md. Serajul Haque (Bhairahawa Campus Journal, 2024)
This study Hydrazine-based piperidine derivatives are widely recognized for their significant roles in pharmaceutical development and material science research. In this context, the present study aimed to synthesize a novel hydrazone derivative to explore its structural and electronic features. This study presents the synthesis and structural characterization of (E)-1-(4-((2-(2,4-Dinitrophenyl)hydrazono)methyl)phenyl)piperidine) (DHP). The compound was obtained through a condensation reaction between 4-(piperidin-1-yl) benzaldehyde and (2,4-dinitrophenyl) hydrazine, achieving an 88% yield. Its structure was confirmed using ¹H NMR, ¹³C NMR, FT-IR, and UV-Vis spectroscopy. Molecular electrostatic potential (MEP) analysis highlighted regions of charge distribution, with electronegative zones concentrated around nitro (-NO₂) groups and electropositive areas near the hydrazone linkage. The UV-Vis spectrum exhibited a peak at 406 nm, attributed to π–π* transitions and intramolecular charge transfer. The results validate the successful synthesis and structural integrity of DHP, underscoring its significance in organic synthesis, photophysical investigations, and material science.